Rancang Bangun Sistem Kendali Jarak Jauh Semi Autonomous Pada Prototype Kapal Penebar Pakan Ikan Bandeng - Mahsun, Ali; Nur, Mohammad; Jauhari, Moh (Techno Bahari, 2024)
Ponds are artificial ponds that are used as a means of aquaculture. For people who are engaged in aquaculture, providing sufficient feed is very important for the smooth running of fish farming. Until now, fish feeding is still using a manual system, so there is a lack of time efficiency and less distribution. Therefore fish farmers need a tool that can spread the feed with a remote controlled system so that in this way it will provide time efficiency and can be evenly distributed. In making this final project I will make a tool that can help fish farmers to spread the feed using a remote control boat using Arduino, in this ship there are several components and auxiliary tools namely Arduino, NRF24L01, PA Wireless Module, Antenna , 100uF Capacitor Condenser, Arduino Joystick, Battery, Battery Capacity Tester, Electronic Speed ??Controller (ESC), Servo, DC Motor, Boat Steering, Arduino Application. Thus this tool will greatly assist fish farmers in the process of stocking feed so that they can assist the cultivation process until the harvesters arrive with satisfactory results.